Environmental noise in hospitals: a systematic review - de Lima Andrade, Erik [UNESP]; da Cunha e Silva, Darllan Collins [UNESP]; de Lima, Eligelcy Augusta [UNESP]; de Oliveira, Renan Angrizani [UNESP]; Zannin, Paulo Henrique Trombetta; Martins, Antônio Cesar Germano [UNESP] (Springer Nature, 2021)
Environmental noise has been growing in recent years, causing numerous health problems. Highly sensitive environments such as hospitals deserve special attention, since noise can aggravate patients’ health issues and impair the performance of healthcare professionals. This work consists of a systematic review of scientific articles describing environmental noise measurements taken in hospitals between the years 2015 and 2020. The researchers started with a consultation of three databases, namely, Scopus, Web of Science, and ScienceDirect. The results indicate that for the most part, these studies are published in journals in the fields of medicine, engineering, environmental sciences, acoustics, and nursing and that most of their authors work in the fields of architecture, engineering, medicine, and nursing. These studies, which are concentrated in Europe, the Americas, and Asia, use as reference values sound levels recommended by the World Health Organization. Leq measured in hospital environments showed daytime values ranging from 37 to 88.6 dB (A) and nighttime values of 38.7 to 68.8 dB (A). Leq values for outdoor noise were 74.3 and 56.6 dB (A) for daytime and nighttime, respectively. The measurements were taken mainly inside hospitals, prioritizing more sensitive departments such as intensive care units. There is a potential for growth in work carried out in this area, but research should also include discussions about guidelines for improvement measures aimed at reducing noise in hospitals. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Acoustics; Environmental noise; Hospital environment; Noise pollution; Public health; Sound pressure level